Income Distribution and Regional Convergence in Poland and the European Union - Godziszewski, Bartosz; Kruszka, Michał; Puziak, Marcin (Olsztyn Economic Journal, 2013)
The main aim of this paper is to analyze regional convergence in the period 1995-2007 in Poland and European Union. Main hypothesis is statement that convergence (understood as reducing income disparities) perceived from system wide perspective is not identical with diminishing income disparity among inhabitants of regions in particular countries, even though broad range of EU cohesion policy means were applied. The analysis was carried out in several steps. Initially, the authors referred to the classical convergence hypotheses (unconditional ß convergence) within the EU-27, then the same assumptions were examined taking into account population - weighted indicators. However, the main aim of research undertaken in this study was to investigate the regional (within - country) distribution of income for the selected years. The results allows to state that despite growing mean income in the analyzed systems (EU-27 and Poland ) and strong support by EU funding, one can observe increased disparities between regions.